Book Reviews (Historia, 2021)
1. Medlicott. W . N . . British Foreign Policy Since Versailles. 1919-1963 2. Gordon Brown. A . . The Cape Sketchbooks of Sir Charles D'Oyly. depicting Cape Town. the countryside and neighbouring villages3. Mamillan. W . M .. The Cape Colour Question 4. Thompson. G .. Travels and Adventures in South Africa 5. Gordon. R . F . . Shepstone. the Role of the Family in the History of South Africa 1820-1900 6. Newton Thompson. J.. The Story of a House 7. Glass. L . D . S .. The Matabele War 8. Wilman. M . . The Rock Engravings of Griqualand West and British Bechuanaland9. Picard. H . W . J . . Gentleman's Walk. the Romantic Story of Cape Town's Oldest Street. Lanes and Squares